2020
DOI: 10.1002/nop2.489
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain 1–5 years after heart transplantation—A nationwide cross‐sectional cohort study

Abstract: Aim To provide a multidimensional assessment of self‐reported chronic pain 1–5 years after heart transplantation and its relationship with self‐reported well‐being, fatigue, recovery, self‐efficacy and socio‐economic factors and to explore differences between heart recipients and a cohort of lung recipients. Design This multicentre, cross‐sectional, cohort study is a part of the Swedish national Self‐management after thoracic transplantation study. Methods Six questionnaires were distributed at the heart recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 44 publications
4
13
2
Order By: Relevance
“…In contrast to previous research on symptom distress [20] and chronic pain [8], there were hardly any gender differences regarding symptom distress. The significant gender difference pertaining to increased appetite presumably lacks clinical relevance as the median score was 0 in both groups, indicating no problems at all.…”
Section: Gender Differencescontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous research on symptom distress [20] and chronic pain [8], there were hardly any gender differences regarding symptom distress. The significant gender difference pertaining to increased appetite presumably lacks clinical relevance as the median score was 0 in both groups, indicating no problems at all.…”
Section: Gender Differencescontrasting
confidence: 99%
“…The HTRs most burdened are those younger than 50 years, not working and living alone. This pattern was also seen regarding chronic pain after HTx [8]. Could it be that younger HTRs experience a pressure to return to work as well as having different conditions regarding family life and parental strain, leading to a greater challenge in terms of social adaptation?…”
Section: Symptom Occurrence In Different Sub-groupsmentioning
confidence: 83%
See 1 more Smart Citation
“…Fatigue among female HTRs has been shown to be associated with physiological and psychological factors [ 15 ]. Women are also more burdened by chronic pain after HTx [ 32 ], thus highlighting the need to specifically focus on female HTRs when supporting symptom management.…”
Section: Discussionmentioning
confidence: 99%
“…This was somewhat surprising based on our clinical experience where HTRs are often viewed as being in a much better position than LuTRs in terms of survival, complications and the risk of graft rejection. However, previous studies in the SMATT project have revealed a tendency for HTRs to experience more pain than LuTRs [ 32 ] and that LuTRs seem to adapt and manage their symptoms faster than HTRs [ 35 , 36 ]. This highlights the importance of exploring the differences between HTRs and LuTRs to deeper the understanding of the struggles in their respective recovery processes.…”
Section: Discussionmentioning
confidence: 99%